Treatment outcome in depressed alcoholics - Hesselbrock, M (Alcoholism-Clinical and Experimental Research, 1987)
Keywords: dept.swk; ⛔ No DOI found

Alcoholism and Substance-Abuse - Course and Outcome - Hesselbrock, V; Hesselbrock, M (Alcoholism-Clinical and Experimental Research, 1987)
Keywords: dept.swk; ⛔ No DOI found

Effects of retesting with the beck and zung depression scales in alcoholics - Choquette, Keith A; Hesselbrock, Michie N (Alcohol and Alcoholism, 1987)
The present study assessed the presence of testing effects arising from the repeated administration of both the Beck and Zung depression scales to a group of 60 inpatient alcoholics. Thirty-seven men and 23 women were randomly assigned to one of three groups and administered the depression scales on one, two or three occasions, in successive weeks of treatment. Although the between group comparisons of initial test administration did not indicate a true change in depression, a within group comparison of initial with subsequent test administrations indicated a clear improvement in depression scores on both scales. Apparently the result of the reactive effects of testing, the within group differences could easily mislead a researcher into believing depression was alleviated when in fact it was not. This sizeable testing effect has obvious implications for studies which repeatedly assess depression. © 1987 Medical Council on Alcoholism.
Keywords: Adult; Aged; Aged, 80 and over; Alcoholism; Depressive Disorder; Emotions; Female; Hospitalization; Human; Male; Middle Age; Psychiatric Status Rating Scales; Support, U.S. Gov't, P.H.S.; Time Factors; adult; aged; alcoholism; article; clinical trial; depression; dept.swk; emotion; female; hospitalization; human; male; randomized controlled trial; rating scale; time; ⛔ No DOI found